Islamophobia and the use of the Qur’anic text: A critical discourse analysis of distortion mechanisms and their impact on Western perception - Khalaf, Mahmood Matnee; Shabeeb, Taha Ibrahim; Saged, Ali Ali Gobaili (Research Journal in Advanced Humanities, 2026)
This research aims to analyze the phenomenon of Islamophobia by tracing the mechanisms of employing the Qur’anic text within Islamophobic discourse, and revealing the patterns of semantic and interpretive distortion practiced on the text in contemporary Western media and cultural contexts. The research begins with the premise that this discourse not only extracts Qur’anic texts from their historical and interpretive contexts, but also goes further, reproducing them within pre-existing narrative and ideological frameworks that contribute to perpetuating negative stereotypes about Islam and Muslims, and reshaping the meaning of the text to serve preconceived notions of violence or exclusion.This research employs a critical analytical approach, drawing on critical discourse analysis methodologies. It examines selected Quranic verses that are among the most frequently cited texts in Islamophobic debates, comparing them with their interpretations in the Islamic exegetical tradition and contextual understanding methodologies. The research also addresses prominent patterns of methodological distortion, such as contextual selectivity, biased translation, cultural generalization, and the imposition of contemporary meanings onto the texts. Furthermore, it deconstructs the mechanisms by which religious texts are exploited for media and political purposes.The research concludes that the use of Quranic texts in Islamophobic discourse directly contributes to shaping Western perceptions of Islam by producing distorted cognitive representations based on a fragmented and unscientific reading of religious texts. It emphasizes that these practices do not represent mere differences in interpretation but rather reflect a discursive structure that produces ideological meaning. The research concludes by stressing the importance of developing contemporary interpretive and critical approaches capable of deconstructing this discourse and reinterpreting the Quranic text within its integrated epistemological, humanistic, and rhetorical context.